THE USE OF REDUCE DIFFERENTIAL TRANSFORM METHOD FOR SOLVING PARTIAL DIFFERENTIAL EQUATIONS - HUSSEIN, NOOR ALI (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper, we apply Reduced Differential Transform Method (RDTM) for solving partial differential equations (Heat equation with external force ) , many numerical application are shown for implementing this method. The results show that this method is very effective and simple .